Integrating multi-source data through a geomechanical digital twin: advancing risk management in cave mining - Monsalve, J.; Vanegas, C.; Lemas-Pesqueira, C.; Hilt, G.; Ferguson, S.; Shea, N. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Cave mining involves highly interdependent processes, making geomechanical risk management complex and dynamic. To address these challenges at Henderson mine, a geomechanical digital twin was developed to integrate production, cave development, geomechanical modelling, and monitoring data into a unified platform. A digital twin is a dynamic, virtual model that represents the state and behaviour of a physical system. In the context of caving, it is a near-real-time representation of the underground environment, continuously updated through the exchange of data between digital and physical domains. This system enhances the understanding of the caving process and strengthens communication across technical and operational teams. By leveraging real-time and historical datasets, the digital twin enables better informed decision-making and provides improved forecasting capabilities for early identification and prioritisation of geomechanical risks. This paper provides an update on the current state of the Henderson mine and discusses current cave management practices in this operation. The Henderson geomechanical digital twin is described with each of its components explained. Finally, a series of applications where this digital twin has supported the operation is discussed. This platform promotes collaboration between engineering and operations, supporting proactive planning and timely response strategies. This contributes to improved management of caving operations, increasing safety and operational efficiency.